Freeze to defrost! Negating the asset form - Geraldine Juárez (Finance and Society, 2023)
Assets thrive on liquidity but they also enact a freezing of their own, a freezing of the underlying. How can we undo the cold reign of the asset economy? By turning state practices of asset freezing into the basis for a pirate tactic of de-assetization. De-assetization means freezing over the pipes that keep capital circulating; it also means applying heat to the notion that everything in the world can and should be frozen in order to release more liquid flows of cash.
Keywords: 300; Asset freezing; assetization; capitalization; de-assetization; negation; temporality